What Defines the Philosophy of Science – Positive Epistemic, Evidence Generation, or a Combination of Both? - Sunil Kumar Raina; Raman Kumar (Journal of Applied Sciences and Clinical Practice)
The idea of evidence-alone being central to generation of scientific knowledge in general and medical-scientific knowledge in particular may not have a historical context to it and therefore needs to be looked into.